Long Cold Ischemia Times in Same Hospital Deceased Donor Transplants - Chow, Eric KH (Transplantation, 2018)
BACKGROUND: Recent changes in deceased donor organ allocation for livers (Share-35) and kidneys (KAS) have resulted in broader sharing of organs and increased cold ischemia time (CIT). Broader organ sharing however is not the only cause of increased CIT. METHODS: This was a retrospective registry study of CIT in same-hospital liver transplants (SHLT, n=4,347) and kidney transplants (SHKT, n=9,707) between 2004 and 2014. RESULTS: In SHLT, median (IQR) CIT was 5.0 (3.5–6.5) hours versus 6.6 (5.1–8.4) hours in other-hospital LT. DCD donors, donor biopsy, male recipient, recipient obesity, and previous transplant were associated with increased CIT. MELD at transplant of 29+ or status 1a was associated with decreased CIT. SHLT CIT varied by OPO and transplant-center (p<0.01), with center median CIT ranging from 2.0 – 7.8 hours across 118 centers. In SHKT, CIT was 13.0 (8.5–19.0) hours versus 16.5 (11.3–22.6) hours in other-hospital KT. Overweight donors, DCD donors, right-kidney, donor biopsy, recipient obesity, use of mechanical perfusion, additional KT procedures on the same day, and transplant center annual volume were associated with increased CIT. Older donor age, ECD donors, and underweight recipients were associated with decreased CIT. SHKT CIT varied by OPO and transplant-center (p<0.001), with center median CIT ranging from 3.3 – 29 hours across 206 centers. Transplant centers with longer SHKT also had longer SHLT (p=0.01). CONCLUSION: Same-hospital transplants already have a significant amount of CIT, even without transporting the organ to another hospital.